2023
DOI: 10.1186/s12944-023-01859-3
|View full text |Cite
|
Sign up to set email alerts
|

Composite lipid indices in patients with obstructive sleep apnea: a systematic review and meta-analysis

Abstract: Background One of the most prevalent sleep disorders affecting the individual’s daily life is obstructive sleep apnea (OSA), for which obesity is a major risk factor. Several novel lipid indices have been suggested to have associations with OSA, among which visceral adiposity index (VAI), atherogenic index of plasma (AIP), and lipid accumulation product (LAP) are the most important ones. Herein, the current study aimed to systematically investigate the association between these indices and OSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Our analysis supports the role of the TyG index in diagnosing OSA and the diagnostic ability of this index is comparable to that of other anthropometric indices, such as waist-to-hip ratio, WC, and BMI [ 56 58 ], or other lipid indices like the visceral adiposity index (VAI), the lipid accumulation product (LAP), or atherogenic index of plasma (AIP) [ 59 ]. Notably, as a result of our analysis, the TyG index is significantly higher in patients with OSA with an SMD of 0.86 (95% CI: 0.58–1.13), confirming the relationship between components of metabolic syndrome (triglyceride and glucose) and OSA, which has also been suggested previously [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 78%
“…Our analysis supports the role of the TyG index in diagnosing OSA and the diagnostic ability of this index is comparable to that of other anthropometric indices, such as waist-to-hip ratio, WC, and BMI [ 56 58 ], or other lipid indices like the visceral adiposity index (VAI), the lipid accumulation product (LAP), or atherogenic index of plasma (AIP) [ 59 ]. Notably, as a result of our analysis, the TyG index is significantly higher in patients with OSA with an SMD of 0.86 (95% CI: 0.58–1.13), confirming the relationship between components of metabolic syndrome (triglyceride and glucose) and OSA, which has also been suggested previously [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 78%
“…This study reveals a positive association between VAI, LAP, and OSA, consistent with findings by Deng et al Hence, both indices should be considered in clinical OSA management [ 21 ]. “Previous meta-analyses have also reported the similar findings [ 39 ], suggesting that lipid indexes, including LAP and VAI, possess commendable diagnostic capability ies. For the research findings, this study compared and discussed them with relevant literature.…”
Section: Discussionsupporting
confidence: 68%
“…The present study revealed that in patients with OSA, those in LVH group and concentric LVH group had higher levels of AHI and higher prevalence of moderate to severe OSA, which is largely consistent with previously published results. Moreover, a recent meta-analysis demonstrated that AIP was significantly higher in patients with OSA and increased with the severity of OSA [ 30 ]. Largely in line with those results, the level of AHI and the prevalence of moderate to severe OSA in the present study was increased gradually from the lowest AIP tertile group to the highest AIP tertile group, although there was no significant statistical difference due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%